Penerapan model problem-based learning bermuatan budaya lokal untuk meningkatkan kemampuan pemecahan masalah peserta didik - Yuliantini, Cewang; Murni, Atma; Nur Siregar, Syarifah (Karoteh Utama, 2025)
This study aims to improve the learning process and enhance students' mathematical problem-solving skills through the implementation of a Problem Based Learning (PBL) model integrated with local cultural values. The research employed a classroom action research design consisting of two cycles conducted during the odd semester of the 2024/2025 academic year. The subjects were 35 students, and data were collected through observation sheets and problem-solving tests. The learning tools used included a teaching module. The results showed continuous improvement in classroom activities, such as students' ability to understand problems presented in the worksheets, increased collaboration among group members, greater student engagement in discussions, and attentiveness to instructions and learning tasks. The average problem-solving test scores improved from an initial 21.52 to 77.26 in the first cycle and 86.76 in the second cycle. These findings indicate that the implementation of the PBL model with local cultural content effectively improves both the learning process and students’ mathematical problem-solving abilities.